Effect of the antifungal drug ciclopirox on the inhibition of HMGA2-mediated oncogenic capacity in ACHN renal cell carcinoma - Liu, Xujie; Su, Jiahao; Song, Lingling; Fu, Qizhong; Li, Xuan; Li, Junying; Liu, Ying; Liao, Jingyi (Frontiers in Pharmacology, 2026)
Ciclopirox olamine (CPX), an off-patent antifungal agent with a broad antimicrobial spectrum, is used to treat fungal infections. In addition to its antifungal effects, it inhibits tumor growth. However, little is known about the direct target proteins and anticancer mechanisms of CPX. The non-histone chromatin protein encoded by HMGA2, known as human high-mobility group A2, plays a crucial role in various biological processes such as cell cycle regulation, apoptosis induction, DNA damage repair, and the process of epithelial-mesenchymal transition. Increased HMGA2 expression is closely linked to tumor advancement, unfavorable prognosis, and inadequate response to therapeutic interventions. We found that CPX inhibited the level of the transcriptional regulator E2F1 in renal cancer cells by downregulating the expression of HMGA2, which led to a decrease in the expression of cell cycle protein D1 (CyclinD1) and cell cycle-dependent kinase 6 (CDK6), causing cell cycle disorders in renal cancer cells. Additionally, CPX significantly inhibited the proliferation, migration, and invasion of renal cancer cells in vitro. We also found that CPX exerted anti-tumor effects by inhibiting renal cancer cell proliferation and epithelial-mesenchymal transition (EMT) in in vivo xenograft mouse experiments. The TGF-β/Smads signaling pathway is linked to this phenomenon. These results provide robust evidence highlighting the potential for repurposing CPX in cancer treatment.